Effect of shrimp chitosan coating on physicochemical properties and shelf life extension of banana - Sikder, Md. Belal Hossain; Islam, Md. Muksitu; Rashid, Shah Samiur; Moazzem, Md. Shakir (Penerbit Universiti Malaysia Pahang, 2019)
Banana is a highly perishable fruit with short shelf-life. Lack of proper preservation practices results in considerable amount of post-harvest loss of banana in Bangladesh. To minimize this post-harvest loss and extend the shelf-life of mature bananas (green colour) were treated with 0.5%, 0.75% and 1% chitosan coating and stored at room temperature (28±2ºC). The viability of the coating in extending the fruits shelf-life was assessed by evaluating total weight loss, ash content, total soluble solids ( ̊Brix), pH, titratable acidity (%), disease severity and shelf-life during the storage period. Chitosan coating Reduced respiration activity, thus slow ripening and the rate of decay reduces due to senescence. The chitosan-coated banana samples had a better outcome on weight loss, ash content, total soluble solids ( ̊Brix), pH, titratable acidity (%) and disease severity values as compared to control samples. Banana coated with 1% chitosan exhibited less weight loss and reduced darkening than other samples. Disease severity was remarkably reduced by 1% chitosan coating application. Chitosan coating could extend the shelf-life of banana up to 16 days. This investigation showed that 1% chitosan was very effective in prolonging the shelf-life and quality of banana during the entire storage period.